Reliability of tooth cementum rings to age bighorn sheep: a blind test - John D. Wehausen; Christopher J. O’Brien; Dale R. McCullough (California Fish and Wildlife Journal)
Tooth cementum rings often have been considered the most reliable method for aging larger mammals. Tests of this approach have used samples of known ages, but to ensure objectivity this needs to be carried out as truly blind tests. That has not always been the case, including for North American wild sheep in studies that concluded that cementum ring aging provided highly accurate ages. This study re-examined cementum ring aging accuracy for bighorn sheep (Ovis canadensis) via a blind test of known-age samples from two ecologically different regions in California, using three different laboratory techniques (histological, petrographic, and grinding), and different individuals applying each of those methods. Overall, there were considerably more errors than previously reported. The grinding method performed particularly poorly, but statistical analyses of aging errors for the other two methods found differences between those methods and between the two data sets used. While the histological method had the highest overall rate of correct ages at 31%, its error range was twice that of the petrographic method. Given the error rates we found, cementum-based ages of bighorn sheep should not be treated as accurate ages. It is therefore unlikely that cementum-based ages will improve ages based on horn rings for most male specimens. Cementum-based ages may be useful for female bighorn sheep older than 4-6 years because of difficulties in aging by horn rings.